1990
DOI: 10.1063/1.459325
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-light-induced oxide formation on GaAs surfaces

Abstract: We present a study of deep-ultraviolet-light-enhanced (4.1 < hv < 5.1 eV) oxygen reactions on GaAs from submonolayer to several monolayers coverage. The reaction is nonthermal and does not involve gas-phase excitation or dissociation of O 2 , Our experiments show a distinct wavelength and coverage dependence for the photoenhancement. X-ray photoelectron spectroscopy has been used to examine the chemical nature of the oxygen adsorbate and the GaAs oxides in order to find intermediate reaction species and eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 58 publications
4
16
0
Order By: Relevance
“…Saturation magnetization, coercivity, and remanence values are listed in Table 4. For the core-shell NC/Si sample (S2), the irradiation-induced reduction in saturation might be expected since the shell changes from a ferrimagnetic material (Fe 3 O 4 ) 59 to an antiferromagnetic material (FeO). Note that for bulk FeO the Néel temperature (T N ) is 198 K, but it has been shown that thin FeO layers with Fe on either side show T N well above room temperature due to exchange interactions with FM spins.…”
Section: Results and Discussion A Structural Characterizationmentioning
confidence: 99%
“…Saturation magnetization, coercivity, and remanence values are listed in Table 4. For the core-shell NC/Si sample (S2), the irradiation-induced reduction in saturation might be expected since the shell changes from a ferrimagnetic material (Fe 3 O 4 ) 59 to an antiferromagnetic material (FeO). Note that for bulk FeO the Néel temperature (T N ) is 198 K, but it has been shown that thin FeO layers with Fe on either side show T N well above room temperature due to exchange interactions with FM spins.…”
Section: Results and Discussion A Structural Characterizationmentioning
confidence: 99%
“…Some films have also been made to contain nanophases of Fe 3 O 4 by including nanoparticles in the target for pulsed laser deposition (PLD) [18] or by using a special substrate [19]. A number of studies have used assembled nanoparticles of Fe 3 O 4 that were sufficiently small that they would be in the superparamagnetic regime at RT in order to study the magnetoresistance [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Samples appeared to be unsaturated even at 30 kOe, likely due the ferrimagnetic nature of Fe 3 O 4 . 27 The estimated saturation magnetization is low compared to theoretical magnetite, however, probably a result of the low Fe/O ratio in the film.…”
Section: Resultsmentioning
confidence: 99%